BrdU-induced hyperlocomotion in the stroked rat. (11th June 2019) - Cooperrider, Jessica; Chan, Hugh H.; Gale, John T.; Park, Hyun-Joo; Baker, Kenneth B.; Machado, Andre G.
Highlights: BrdU is commonly used to label newly-divided cells and has known toxic effects. We show that BrdU administered to adult, stroked animals induced hyperactivity. Caution is urged when interpreting behavioral results post-BrdU administration. Abstract: 5-bromo-2′-dexoyuridine (BrdU) is often used in neuroscience research as a marker of newly-divided cells. However, several studies suggest that BrdU can produce unwanted side effects, including changes in animal behavior and cellular function. In this study, we investigated the effect of BrdU injections on locomotor behavior in a rodent model of ischemic stroke. Ischemic strokes were induced in adult rats, and 50 mg/kg BrdU was intraperitoneally injected over 5 days beginning 2 weeks post-stroke, while control animals received vehicle. Locomotor activity was evaluated by videotaping the rats in their home cages for 30 min, beginning one hour after BrdU injection. BrdU-injected rats showed a nearly three-fold increase in locomotor activity compared to control animals. These findings suggest that BrdU induces a hyperlocomotor effect in rats following brain injury, pointing to the need for caution when interpreting behavioral results in such studies.